Elderly suicide in Sri Lanka in 2016: Modes, reasons and nature of occupation - De Silva, T.H.A.S. (University of Colombo, Sri Lanka., 2019)
Elderly people have a higher risk of committing suicide than any other age group worldwide. In Sri Lanka, 60 years and above is considered the demarcation age in identifying the elderly population. Suicides among adult males have significantly contributed to the rise in suicides (Thalagala, 2009). In current suicide trends, an increasing trend in elderly suicide rates in Sri Lanka could be identified. Therefore, the main objective of this study to investigate modes of suicides, reasons for suicides and the nature of occupation of those who commit suicide, with special reference to suicides among the elderly people in Sri Lanka. This study is based on secondary quantitative data obtained from the Department of Police in 2016. Reporting suicides to the police is mandatory in Sri Lanka and these reports are systematically collected in a data base at the Statistical Division of the Department of Police. The sample size is 734 elderly suicide cases including 620 males and 114 females who were above the age of 60. According to the reported suicide cases, a majority of the elderly suicide mode was strangling (45.5%). Most of the suicide cases were reported among male elders (84.5%) with female elderly suicide percentage being 15.5%. Chronic diseases and physical disabilities (29.6%) have been a major reason for elderly suicides. When considering the nature of occupations of the elderly people who committed suicide, a majority of them were unemployed persons (44.3%). 30.9 % of them were not classified by their occupation of whom 26.8 were male and 4.09 percent were female. It is therefore important to address emerging elderly suicide issues in Sri Lanka.
Keywords: elderly, suicide